What Is the Evidence on Natural Recovery Over the Year Following Sports-Related and Non-Sports-Related Mild Traumatic Brain Injury: A Scoping Review - Brady, M; Hume, PA; Mahon, S; Theadom, A (Frontiers Media S.A., 2021)
Background: Treatment approaches often differ dependent upon whether a person experiences a sports-related or a non-sports-related mild traumatic brain injury. It remains unclear if recovery from these injuries is comparable or unique to context of the injury. Objective: To identify knowledge gaps on self-reported outcomes and trajectories between sports- and non-sports-related mild traumatic brain injuries and how they are assessed in adults. Methods: This scoping review used a systematic search of key electronic databases, including PubMed, SPORTDiscus, Embase, MEDLINE, and CINAHL for articles published in 1937 until March 10, 2021. Articles were included if they were available in English; full text published in a peer-reviewed journal; had a prospective or retrospective study design; reported data on mild TBI cases >16 years of age, and included data from at least two time points on self-reported outcomes within 12 months post-injury. A standardized data extraction spreadsheet was used to determine the participant characteristics, definitions, assessment methods, outcomes, and recovery time frames. Results: Following removal of duplicates, the search strategy elicited 6,974 abstracts. Following abstract review, 174 were retained for full text review. Of the 42 articles that met inclusion criteria, 18 were sports related (15 in the USA and three in Canada) and 24 were general population studies (six in USA, three in Canada, three in Australasia, nine in Europe, two in Taiwan, and one in Morocco). Direct comparison in recovery trajectories between the sport and general population studies was difficult, given notable differences in methodology, definitions, types of outcome measures, and timing of follow-up assessments. Only one article reported on both sports-related and non-sports-related traumatic brain injuries separately at comparable timepoints. This study revealed no differences in recovery time frames or overall symptom burden. Discussion: Whilst there is a clear benefit in researching specific subpopulations in detail, standardized outcome measures and follow-up time frames are needed across contexts to facilitate understanding of similarities and differences between sports- and non-sports-related mild traumatic brain injuries to inform clinical treatment.
Keywords: Concussion; Recovery; Review; Sport; Traumatic brain injury